2013
DOI: 10.3892/or.2013.2446
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor genes associated with drug resistance in ovarian cancer (Review)

Abstract: Ovarian cancer is a fatal gynecological cancer and a major cause of cancer-related mortality worldwide. The main limitation to a successful treatment for ovarian cancer is the development of drug resistance to combined chemotherapy. Tumor suppressor genes (TSGs) are wild-type alleles of genes which play regulatory roles in diverse cellular activities, and whose loss of function contributes to the development of cancer. It has been demonstrated that TSGs contribute to drug resistance in several types of solid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 50 publications
1
50
1
Order By: Relevance
“…Many of the genes with increased expression, including granzyme B (GZMB), 29 a calcium binding protein (S100A6), 30 a gap junction protein (GJA1), 31 and a cyclin-dependent kinase inhibitor (CDKN2A), 32 have been reported to have a role in cell death and/or apoptosis. Several genes showing decreased expression, including the inhibitory receptor of peripheral mononuclear cells (LAIR1), 33 a conserved cysteine-rich protein (PLAC8), 34 an apoptosis-associated speck-like protein (PYCARD), 35 and a receptor tyrosine kinase (ERBB3), 36 have also been reported to have a role in cell death. CARD11, a caspase recruitment domain-containing protein, has decreased expression and been reported to interact with the proapoptotic BCL10 protein.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the genes with increased expression, including granzyme B (GZMB), 29 a calcium binding protein (S100A6), 30 a gap junction protein (GJA1), 31 and a cyclin-dependent kinase inhibitor (CDKN2A), 32 have been reported to have a role in cell death and/or apoptosis. Several genes showing decreased expression, including the inhibitory receptor of peripheral mononuclear cells (LAIR1), 33 a conserved cysteine-rich protein (PLAC8), 34 an apoptosis-associated speck-like protein (PYCARD), 35 and a receptor tyrosine kinase (ERBB3), 36 have also been reported to have a role in cell death. CARD11, a caspase recruitment domain-containing protein, has decreased expression and been reported to interact with the proapoptotic BCL10 protein.…”
Section: Resultsmentioning
confidence: 99%
“…For example, on the basis of comprehensive bioinformatic analysis, Yin et al (77) reported that SPARCL1 and CCL21 are associated with drug resistance in ovarian cancer. Similarly, 15 TSGs associated with drug resistance in ovarian cancer were analyzed by comprehensive bioinformatics to overview the relationship of the 15 TSGs with drug resistance and to discover potential TSGs related with drug resistance (49).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of DAPK1 and DAPK2 is altered in multi-drug-resistant gastric cancer cell lines and thus these genes may be an integral part of the mechanisms responsible for chemoresistance (48). In ovarian cancer, DAPK1 has direct interactions with FBXO32, PDCD4, PTEN, TP53 and TP73, and has indirect interactions with BRCA1, BRCA2, CDKN1A, IL24, MLH1 and SULF1, which are all involved in drug resistance in ovarian cancer, suggesting its potential role in drug resistance in ovarian cancer (49). As for CDK2, a previous study revealed that cisplatin consistently induces transient S-phase arrest by inhibiting the CDK2/cyclin A complex in the S-phase at 12 h after treatment with cisplatin or DAP in combination with the mitotic inhibitor nocodazole and also potently inhibits G1-phase CDK2/cyclin E activities at 18 h (50), indicating that CDK2 can directly respond to cisplatin in ovarian cancer cells.…”
Section: Functional Prediction and Analysis Based On Protein/ Gene-prmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, apoptosis, which is associated with the expression of specific 'death' genes and downregulation of 'survival' counterparts, is crucial in determining the response to chemotherapeutic agents (8,9). However, regardless of the mechanisms, abnormal expression of drug resistance-related genes often plays important roles in drug resistance (10).…”
Section: Introductionmentioning
confidence: 99%